Behaviorisme dan Pembentukan Karakter Kristen : Pendekatan Disiplin Positif dalam Pendidikan Gerejawi (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The formation of Christian character in church-based education often faces challenges when disciplinary approaches rely heavily on punishment and external compliance. This article examines the relevance of behaviorism in shaping Christian character through the lens of positive discipline an approach that emphasizes reinforcement of desirable behavior, nurturing relationships, and the development of intrinsic moral awareness. Using a literature review and a small scale case analysis of contemporary church educational practices, this study evaluates how the principles of reinforcement, modeling, and behavioral consistency can be integrated with Christian values such as love, repentance, and the cultivation of conscience. The findings indicate that behaviorism remains useful when applied selectively within a holistic Christian educational theology. Positive discipline aligns more closely with biblical values because it promotes responsible character growth rather than mere obedience. This article contributes to the pedagogical discourse of church education by proposing an integrative framework that combines behavioristic principles with positive discipline to enhance effective and sustainable Christian character formation.